The Impact of β-1,4-Galactosyltransferase V on Microglial Function - Wang, Xiaoyu; Shi, Naiqi; Hui, Meiqi; Jin, Hui; Gao, Shumei; Zhou, Qiao; Zhang, Li; Yan, Meijuan; Shen, Hongmei (Frontiers in Cellular Neuroscience, 2021)
β-1,4 galactosyltransferase V (β-1,4-GalT V) is one of the β-1,4 galactosyltransferase family, which modifies proteins and plays a vital role in biological function. Our previous work revealed that β-1,4-GalT V was expressed in brain tissue, and participated in the recovery of spatial learning and memory in traumatic brain injury rats. However, expression of β-1,4-GalT V in microglia, resident immune cells in central nervous system, and its impact on microglia in resting and LPS-triggered activated stages are elusive. Here, we clarified that β-1,4-GalT V expresses in microglia, and it regulates microglia migration, proliferation, and release of the inflammary factors. We also observed that β-1,4-GalT V affects the expression level of TNFR2 instead of TNFR1. These results strongly support the fact that β-1,4-GalT V is involved in microglial function.